Self-Management Nyeri Pasien Kanker Metode Non Farmakologi - Putri, Prahardian; Muliyadi, Muliyadi; Juliansyah, Rahmad Aswin (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2022)
Cancer is a chronic degenerative disease whose prevalence is currently increasing. In the world, in 2018 there were 18.1 million new cases with 9.6 million deaths. In Indonesia, there are 136.2 cancer patients per 100,000 population, the results of the Riskesdas cancer prevalence are 1.79 per thousand population (Riskesdas 2018). Cancer causes physical, psychological, social, and spiritual problems. One of the physical problems that cause discomfort in cancer patients is pain. The pain problem experienced is related to the disease and the impact of cancer treatment or treatment. Pain impacts physical comfort, sleep rest, and psychological comfort which causes a decrease in the quality of life of cancer patients. Chronic pain experienced by cancer patients requires self-management skills to adapt and minimize the pain experienced. Self-management of pain (relaxation, distraction, and guided imagery) effectively reduces pain. The purpose of this community service is to improve the ability to self-management of pain with relaxation, distraction, and guided imagery. The solution to the problem of pain in cancer patients is carried out in this community service by increasing the ability of cancer patients to self-management of pain. Methods of implementing community service, the community service team develops materials (booklets and videos) for self-management of pain, then trains each patient to use self-management of pain based on the material, and provides self-management assistance for cancer pain. The output target of this community service is to increase the self-management of cancer patient's pain. In addition, it produces booklets and videos of self-management of cancer pain with IPR as well as published results of community service.